Avaliação da capacidade de uso da terra da bacia do córrego do cavalheiro - Analândia, SP - Cunha, Cenira Maria Lupinacci da [UNESP]; Pinton, Leandro de Godoi [UNESP] (My University, 2012)
Environmental factors are important in agriculture and need to be considered for getting good degree of development and reasonable efficiency, by reducing their operating costs. To this end, land use shall be appropriated to the conditions offered by the physical elements of the landscape. By facing such questions, this paper aims is to present of mapping the ability of land use of the hydrographic basins Cavalheiro Stream basin (in the city of Analândia - São Paulo State - Brazil) which presents serious erosion problems. Besides it aims to assess if the current land use in this area is consistent with the identified land use ability. For this we have made a cartographic document that spatializes the various classes of usability and its main restrictions. The correlative analysis between that document and land use data showed that Cavalheiro Stream's current use is predominantly inappropriate with the usability of land, which was identified from the physical attributes of the studied area, except for a few sites that are used for forestry and pasture placed in Western, Eastern and Central-South.

Os fatores ambientais têm papel importante na atividade agrícola e necessitam ser considerados para que essa obtenha bom grau de desenvolvimento e razoável eficiência, através da redução dos seus custos operacionais. Para tanto se faz necessário que o uso da terra seja adequado às condições propiciadas pelos elementos físicos da paisagem. Diante de tais questões, o objetivo desse artigo é apresentar o mapeamento da capacidade de uso da terra da bacia hidrográfica do Córrego Cavalheiro (Analândia-SP) a qual apresenta sérios problemas erosivos. Além disso, objetiva-se avaliar se o uso da terra atual nessa área está condizente com a capacidade de uso da terra identificada. Para isso foi construído um mapa, em escala de 1:10.000, que espacializa as diversas classes de capacidade de uso e suas principais restrições. As análises correlativas entre esse documento e dados de uso da terra buscaram atender os princípios do método sistêmico, realizando uma análise espacial, a qual possibilitou detectar que o atual uso praticado na bacia do Córrego do Cavalheiro encontra-se, predominantemente, inadequado com a capacidade de uso da terra identificada a partir dos atributos físicos da área de estudo, com exceção de algumas áreas utilizadas para a silvicultura e pastagens, existentes no setor oeste, leste e centro-sul.
Assessing the ability of land use: A study on hydrographic basins
Keywords: Analândia (SP); Erosion; Land use; Level of limitation; Slope; agricultural production; cartography; environmental factor; erosion; forestry practice; hydrography; land use; land use planning; river basin; Brazil; Cavalheiro Basin; Sao Paulo [Brazil]